2022
DOI: 10.3892/ol.2022.13552
|View full text |Cite
|
Sign up to set email alerts
|

Low serum albumin levels and high neutrophil counts are predictive of a poorer prognosis in patients with metastatic breast cancer

Abstract: Breast cancer is a severe disease with high incidence and mortality rates in menopausal women. Previous studies have shown that nutritional status and inflammation play a significant role in the development of breast cancer. However, whether serum albumin (ALB) and neutrophils (NE) accelerate the progression of this disease remains unclear.In the present study, a total of 94 cases of newly diagnosed metastatic breast cancer were assessed. For analysis, 26 risk factors including ALB and NE were assessed. Multiv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
10
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(10 citation statements)
references
References 48 publications
0
10
0
Order By: Relevance
“…Low albumin status is a prevalent phenotype in various diseases 9, 10, 11, 12 . Indeed, this is one of the most unfavorable symptoms, suggestive of low nutrition status, observed in patients with advanced cancers 9, 10, 11, 12 . In breast cancers, low albumin status is a prognostic factor 9, 10, 11, 12 .…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Low albumin status is a prevalent phenotype in various diseases 9, 10, 11, 12 . Indeed, this is one of the most unfavorable symptoms, suggestive of low nutrition status, observed in patients with advanced cancers 9, 10, 11, 12 . In breast cancers, low albumin status is a prognostic factor 9, 10, 11, 12 .…”
Section: Discussionmentioning
confidence: 99%
“…Indeed, this is one of the most unfavorable symptoms, suggestive of low nutrition status, observed in patients with advanced cancers 9, 10, 11, 12 . In breast cancers, low albumin status is a prognostic factor 9, 10, 11, 12 . Despite its prevalence, what low albumin status tells us in detail in patients has been largely unexplored.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The reduction in albumin production in cancer has been supported by an in-vivo investigation, wherein mice with tumors exhibited hypoalbuminemia, mostly attributed to a decline in the abundance of liver albumin mRNA [ 36 , 37 ]. The reduction in albumin synthesis will lead to an elevation in TNF-induced micro-vessel permeability, resulting in a decline in serum albumin concentrations [ 35 , 38 ]. Additionally, a prior investigation has indicated that malnutrition among cancer patients can contribute to a reduction in the synthesis rate of serum albumin, hastening its breakdown and thus leading to hypoproteinemia [ 38 ].…”
Section: Discussionmentioning
confidence: 99%
“…Several studies have demonstrated that more neutrophil infiltration of tumors is associated with worse clinical prognosis [ 2 – 4 ]. However, the exact role of neutrophils in the formation of pre-metastatic niche remains unknown.…”
Section: Introductionmentioning
confidence: 99%